2021
DOI: 10.1016/j.cjtee.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of variable angle volar plate and bridging external fixator with K-wire augmentation in comminuted distal radius fractures

Abstract: Purpose Comminuted intraarticular distal radial fractures are difficult to treat conservatively and require operative treatment. This study compared the functional outcomes between variable angle volar plating and external fixator with K-wire augmentation in open reduction and internal fixation. Methods A total of 62 adult patients with comminuted intraarticular distal radius fracture were randomized into 2 groups: volar plate group and external fixator group. These pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Finally, and most importantly, the inclusion criteria among the 14 trials were heterogenous in terms fracture type. Five trials did not report on the fracture type, while study by Mishra et al 36 exclusively reported on AO type C fracture, whereas McFadyen et al 28 exclusively reported on AO type A and rest of the studies reported data on both type A and C fractures. Such heterogeneous distribution of fracture types raises valid concerns on the validity and applicability of our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and most importantly, the inclusion criteria among the 14 trials were heterogenous in terms fracture type. Five trials did not report on the fracture type, while study by Mishra et al 36 exclusively reported on AO type C fracture, whereas McFadyen et al 28 exclusively reported on AO type A and rest of the studies reported data on both type A and C fractures. Such heterogeneous distribution of fracture types raises valid concerns on the validity and applicability of our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 studies, 3 were conducted in the United States, 3 conducted in the United Kingdom, and 1 study each from France, Belgium, Germany, Columbia, Iran, Pakistan, and India. [14][15][16][26][27][28][29][30][31][32][33][34][35][36] There was only one multicenter trial that was conducted in the United States, Canada, and Singapore. The sample size per study ranged from 34 to 461 participants including 352 males and 478 females.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, this is the first single-centre study reporting functional clinical outcomes of DRFs at medium-term follow-up and including beta multivariate regression analysis on a large patient cohort compared to previous published studies on the same topic [12,46,[68][69][70]. Further, all patients enrolled were operated on by the same trauma surgeons and followed according to a standardised institutional postoperative protocol, reducing confounding bias.…”
Section: Discussionmentioning
confidence: 99%